Consider $a_n$ and $b_n$ are two sequences which $\lim _{n \to \infty} a_n = 1$ and $\lim _{n \to \infty} b_n = \infty$ . Can we always use this formula ?

$$ \lim_{n \to \infty} a_n ^{b_n} = e^{\lim_{n \to \infty}(a_n - 1)b_n}$$

Also, when can we use this method for functions ?

A famous case is $a_n = 1+ \frac{1}{n}$ and $b_n = n$ . So $\lim_{n \to \infty}(a_n - 1)b_n = 1$ and $a_n ^{b^n} = e^1 = e$

  • $\begingroup$ The notation (of the right-hand side) is confusing. If you use two limits, make sure you let them go over different letters; as for now, what $n$ belongs to what limit? $\endgroup$ May 5 '17 at 6:11
  • $\begingroup$ @vrugtehagel Yes , Thank you . I edited it . $\endgroup$
    – S.H.W
    May 5 '17 at 6:13
  • $\begingroup$ @JaideepKhare Your mean is L'Hôpital's rule ? $\endgroup$
    – S.H.W
    May 5 '17 at 6:18
  • $\begingroup$ @JaideepKhare No , I don't . $\endgroup$
    – S.H.W
    May 5 '17 at 6:20
  • $\begingroup$ @JaideepKhare Okay , thank you . $\endgroup$
    – S.H.W
    May 5 '17 at 6:29

Yes, this formula can always be used.

Let's take a look at it derivation.It will be clear from the derivation that where it can be used.

$$\text{let}~~L= \lim_{n \to \infty} a_n ^{b_n}$$

$$\ln L= \lim_{n \to \infty} b_n \ln a_n$$ $$\ln L= \lim_{n \to \infty} b_n \ln (1+(a_n-1))$$

Since $a_n \to 1 \implies a_n-1 \to 0$ therefore, we can use the fact that : $$\lim_{x \to 0}\dfrac{\ln(1 + x)}{x}=1$$

We get

$$\ln L= \lim_{n \to \infty} b_n \left(\frac{\ln (1+a_n-1)}{a_n-1}\right)(a_n-1)=\underbrace {\lim_{n \to \infty} \left(\frac{\ln (1+a_n-1)}{a_n-1}\right)}_{=1} \cdot \lim_{n \to \infty} b_n(a_n-1) $$ $$ \implies \ln L= \lim_{n \to \infty} b_n (a_n-1)$$ Hence $$L=e ^{\lim_{n \to \infty} b_n (a_n-1)}$$

  • $\begingroup$ You have wrote $ \ln L= \ln \lim_{n \to \infty} a_n ^{b_n}$ . Then $\ln L = \lim_{n \to \infty} \ln a_n ^{b_n} $ . Can you explain why it is true ? $\endgroup$
    – S.H.W
    May 5 '17 at 6:33
  • 3
    $\begingroup$ @Jaideep You have assumed the limit exists. Could you justify why/if this works if $\lim_{n\to\infty}a_n^{b_n} = \infty$? $\endgroup$
    – adfriedman
    May 5 '17 at 6:36
  • $\begingroup$ @adfriedman If the limit doesn't exist, then the limit in the exponent of $e$ will also not exist $\endgroup$ May 5 '17 at 6:50
  • $\begingroup$ @S.H.W any finite number of operations or functions can be applied in any limit (which are well defined).Both in LHS and RHS. $\endgroup$ May 5 '17 at 6:54
  • $\begingroup$ This is fine if $L\ne 0.$ But if $L=0$ then $\ln L$ does not exist, and $b_n(a_n-1) \to -\infty$ as $n\to \infty.$ E.g. if $a_n=1-1/n$ and $b_n=n^2. $ $\endgroup$ May 5 '17 at 8:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.